IT Essentials Companion Guide v7 - Academy, Cisco (Cisco Press, 2020)
IT Essentials v7 Companion Guide supports the Cisco Networking Academy IT Essentials version 7 course. The course is designed for Cisco Networking Academy students who want to pursue careers in IT and learn how computers work, how to assemble computers, and how to safely and securely troubleshoot hardware and software issues. The features of the Companion Guide are designed to help you study and succeed in this course: · Chapter objectives -Review core concepts by answering the focus questions listed at the beginning of each chapter. · Key terms -Refer to the updated lists of networking vocabulary introduced, and turn to the highlighted terms in context. · Course section numbering -Follow along with the course heading numbers to easily jump online to complete labs, activities, and quizzes referred to within the text. · Check Your Understanding Questions and Answer Key -Evaluate your readiness with the updated end-of-chapter questions that match the style of questions you see on the online course quizzes. This book is part of the Cisco Networking Academy Series from Cisco Press®. Books in this series support and complement the Cisco Networking Academy.
Online resource; Title from title page (viewed April 1, 2020)
Keywords: Information technology; Microcomputers -- Handbooks, manuals, etc; Microcomputers -- Problems, exercises, etc; Electronic data processing; Technologie de l'information; Micro-ordinateurs; Guides, manuels, etc; Micro-ordinateurs; Problèmes et exercices; information technology; Microcomputers; handbooks; exercise books; Handbooks and manuals; Problems and exercises; Guides et manuels; Problèmes et exercices